2021
DOI: 10.1055/a-1543-6362
|View full text |Cite
|
Sign up to set email alerts
|

Associations of the Polymorphisms in ADIPOQ with Circulating Levels of Adiponectin and Lipids: A Meta-Analysis

Abstract: The relationships between the rs266729, rs1501299, and rs2241766 polymorphisms in adiponectin gene (ADIPOQ) and circulating levels of adiponectin and lipids remain to be clarified. Databases including PubMed and Embase were searched for eligible studies. The random-effects model was used, and standardized mean difference (SMD) with 95% confidence interval (CI) was calculated to estimate the differences in circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…The encoded protein, adiponectin, suppresses hepatic glucose production, enhances insulin sensitization, and improves fatty acid oxidation in skeletal muscle 77 . Polymorphisms of the ADIPOQ gene have been suggested to be associated with metabolic traits including phenotypes related to obesity, insulin resistance, and circulating lipids 78–82 . SNPs at ADIPOQ (rs226729, rs1501299, rs3774261, and rs17300539) were associated with improvement of insulin sensitivity (lower fasting insulin and HOMA‐IR) after bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The encoded protein, adiponectin, suppresses hepatic glucose production, enhances insulin sensitization, and improves fatty acid oxidation in skeletal muscle 77 . Polymorphisms of the ADIPOQ gene have been suggested to be associated with metabolic traits including phenotypes related to obesity, insulin resistance, and circulating lipids 78–82 . SNPs at ADIPOQ (rs226729, rs1501299, rs3774261, and rs17300539) were associated with improvement of insulin sensitivity (lower fasting insulin and HOMA‐IR) after bariatric surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies in 2017 [ 41 ] and 2019 [ 42 ] showed that the GG genotype of rs1501299 had low levels of TC. A meta-analysis performed by Su et al [ 43 ] proposed that the T allele carriers of rs1501299 polymorphism had higher levels of HDL-C and adiponectin than GG homozygotes, whereas the G allele carriers of rs2241766 polymorphism had lower levels of HDL-C and adiponectin than TT homozygotes. The above results indicated that the associations between ADIPOQ polymorphisms and lipid levels remain inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…The top prioritized gene in Caucasians is the adiponectin-encoding gene ADIPOQ , located on chromosome 3q27.3 and spanning 15.8 kb. ADIPOQ is composed of three exons and harbors numerous single nucleotide polymorphisms (SNPs) that have been extensively studied in different populations [ 52 , 53 ], with several of these variants showing associations with alterations in adiponectin levels and metabolic syndrome-related phenotypes [ 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 51 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. The intricate effects of adiponectin in the nervous system have raised the hypothesis that functional variants in ADIPOQ could be involved in susceptibility to LOAD.…”
Section: Introductionmentioning
confidence: 99%